Fungsi Magis Alat Reproduksi Manusia dalam Konsep Binary Opposition dan Simbol - Ketut Wiradnyana (Balai Arkeologi Sumatera Utara, 2010)
AbstractDepictions of human reproduction is found in many megalithic buildings. The magical reproductive function is often equated between the phallus and the vulva. It tends to occur in communities that no longer has a cultural context that is consistent with the idea of megalithic. For it is very important to do a review of reproductive function approach to the concept of the symbols and the binary opposition. This is done considering means of reproduction as a symbol that has a different function with each other. Moreover, the concept of binary opposition developed until now.